The evolving female : a life-history perspective - Morbeck, Mary Ellen, 1945-; Galloway, Alison, 1953-; Zihlman, Adrienne L. (Princeton, N.J. : Princeton University Press, 1997)
A human female is born, lives her life, and dies within the space of a few decades, but the shape of her life has been strongly influenced by 50 million years of primate evolution and more than 100 million years of mammalian evolution. How the individual female plays out the stages of her life--from infancy, through the reproductive period, to old age--and how these stages have been formed by a long evolutionary process, is the theme of this collection. Written by leading scholars in fields ranging from evolutionary biology to cultural anthropology, these essays together examine what it means to be female, integrating the life histories of marine mammals, monkeys, apes, and humans. The result is a fascinating inquiry into the similarities among the ways females of different species balance the need for survival with their role in reproduction and mothering. The Evolving Female offers an outlook integrating life history with an intimate examination of female life paths. Behavior, anatomy and physiology, growth and development, cultural identity of women, the individual, and the society are among the topics investigated. In addition to the editors, the contributors are Linda Fedigan, Kathryn Ono, Joanne Reiter, Barbara Smuts, Mariko Hiraiwa-Hasegawa, Mary McDonald Pavelka, Caroline Pond, Robin McFarland, Silvana Borgognini Tarli and Elena Repetto, Gilda Morelli, Patricia Draper, Catherine Panter-Brick, Virginia J. Vitzthum, Alison Jolly, and Beverly McLeod.
What is life history? -- Life history, the individual, and evolution / Mary Ellen Morbeck -- Changing views of female life histories / Linda Marie Fedigan -- What it means to be a mammal -- Sea lions, life history, and reproduction / Kathryn Ono -- Life history and reproductive success of female northern elephant seals / Joanne Reiter -- What it means to be a primate -- Social relationships and life histories of primates / Barbara B. Smuts -- Development of sex differences in nonhuman primates / Mariko Hiraiwa-Hasegawa -- The social life of female Japanese monkeys / Mary S. McDonald Pavelka -- Natural history of apes : life-history features in females and males / Adrienne L. Zihlman -- What it means to be a catarrhine -- Reading life history in teeth, bones, and fossils / Mary Ellen Morbeck -- The cost of reproduction and the evolution of postmenopausal osteoporosis / Alison Galloway -- The biological origins of adipose tissue in humans / Caroline M. Pond -- Female primates : fat or fit? / Robin McFarland -- What it means to be a human -- Women's bodies, women's lives : an evolutionary perspective / Adrienne L. Zihlman -- Sex differences in human populations : change through time / Silvana M. Borgognini Tarli and Elena Repetto -- Growing up female in a farmer community and a forager community / Gilda A. Morelli -- Institutional, evolutionary, and demographic contexts of gender roles : a case study of!Kung bushmen / Patricia Draper -- Women's work and energetics : a case study from Nepal / Catherine Panter-Brick -- Flexibility and paradox : the nature of adaptation in human reproduction / Virginia J. Vitzthum -- Life history, females, and evolution -- Social intelligence and sexual reproduction : evolutionary strategies / Alison Jolly -- Life history, females, and evolution : a commentary / Beverly McLeod.
Includes bibliographical references (pages 277-325) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Human evolution; Women -- Evolution; Females -- Physiology; Women's studies -- Biographical methods; Êtres humains -- Évolution.; Femmes -- Évolution.; Femelles -- Physiologie; Études sur les femmes -- Histoires de vie; SOCIAL SCIENCE -- Anthropology -- Physical; SCIENCE -- Life Sciences -- Evolution; Women -- Evolution; Females -- Physiology; Women's studies -- Biographical methods; Homme -- Evolution; Femmes -- Evolution; Femelles -- Physiologie; Etudes sur les femmes -- Methode biographique; Human evolution; Females -- Physiology; Human evolution; Women -- Evolution; Women's studies -- Biographical methods; Säugetiere; Weibchen; Evolution; Frau; Vrouwen; Evolutie; Vergelijkende fysiologie; Homme -- Origines; Femmes -- Évolution.